Development of Creative Learning Media Durita Story to Improve Student’s Storying Ability - Putri, Syafira Auliah; Dewi, Happy Indira (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research is motivated by the problem that almost 75% of students need help to develop their ideas assembled into a story and not supported by creative learning media, so students become passive in the learning process. This causes the low ability of students to tell stories. The purpose of this study was to determine the creation of creative learning media in the form of Durita, to find out how valid Durita’s media was, find out how much-increased storytelling ability in grade 5 SDIT Al-Zahiyah using Durita’s media was, and to determine student responses to Durita. The method used is Research and Development (RnD) with a 4D development model (Define, Design, Development, and Dissemination). Based on the objectives described, the making of Durita goes through several stages, such as designing pictures and guidebooks, initial media design, and making media. Another result obtained is a validation test by media experts with a score of 86% in the valid category and a validation test by material experts with a score of 100% in a very valid category. This shows that Durita’s media deserves to be tested on students. The oral pretest and posttest improvement test conducted by students using N Gain were calculated with a score of 0.70 with very high improvement criteria. Student response questionnaire with results as much as 92% with very good criteria and the impression from students that Durita’s media is an exciting and fun medium. The results of this study indicate that Durita’s media is a feasible media to use and can improve students’ storytelling skills, making students happy.